(3JbjjO Gdeged hJejjR GdeTcds - (3CHh Ydj GdMSjf Hf eMeO Hf CMeO GdZSGfj GdCfOdSj, GdLjGfj,J (B498 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg CHj MGJe GdQGRi ai cJGHg Qhi dg Sde HGH HQjO hHQjO hjQfO hjRjO hJRjO s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3HGH fSN GdcdGe ai GdUdGg hGdMOjK jQhjg eMeO Hf YHO dGdg hcPdc CNQLg GdHNGQi ai GdLGeY Yf s
(3GdfSNI HgG MhGTs
(3ai hSWgG SeGY Ydi GdMGaX YHO GdYXje GdefPQi SfI (B638s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B470s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs